Design of An Automatic Temperature Recorder for Fishery Vessels Using Internet of Things Technology - Hadi Purwanto; Maman Hermawan; Chandra Nainggolan; Berbudi Wibowo (Journal of Applied Engineering and Technological Science (JAETS), 2024)
Fishery products, especially capture fisheries, must be safe and high-quality. The treatment of captured fish from capture to consumption is crucial to maintaining its quality. Temperature impacts fish quality. Fish putrefaction can be prevented at a specific temperature. Maintaining optimal fish quality requires temperature monitoring at the holding hatch of fish captured on board. Indonesia requires hatches with fish storage to have automatic temperature recorders and monitors. Inspections by authorities who issued certifications of acceptable fish handling practices found many breaches on Indonesian fishing vessels without automatic temperature monitoring systems. Indonesian fishery exports to the EU have been rejected due to the lack of automatic temperature recording systems on fishing vessels. Existing automatic temperature recording equipment for fishing vessels does not meet technical and legal requirements.  The lack of autonomous temperature monitoring devices on fishing vessels was solved via design thinking in an exploratory study. Thus, fishing vessel temperature recording devices were designed using Internet of Things technology. Literature is utilized to choose resources. Hatch temperature recorder, MAX 31865 module, and PT100 thermocouple sensor use ESP 32 as a microprocessor. Raspberry Pi4 controls, displays, and stores data. This fish hatch temperature recorder has a GPS module for coordinates. This utility manages display and storage with Home Assistant software. Commercial low-temperature recorders are utilized for comparison testing. Before calibration, the pesuotokapi tool had a variance coefficient of 9.39%, whereas the comparison tool had 12.09%. The pesuotokapi tool has a coefficient of variation of 11.96% after calibration, whereas the comparison tool had 13.28%. The pesuotokapi tool regularly yields a lower coefficient of variation than the comparison tool. This shows that the pesuotokapi tool generates data with less divergence from the average recorded temperature than the comparison tool. Pesuotokapi devices regularly outperform comparator devices in temperature before calibration, improving fish hold quality.